Synthesis and characterization of 1,2-benzylidenedioxy-7-(2-hydroxybenzylideneamino)-4-azaheptane and its complexes with transition metals - Boybay, M; Sekerci, M (Pleiades Publishing Ltd, 2002)
1,2-Benzylidenedioxy-7-(2-hydroxybenzylideneamino)-4-azaheptane was synthesized by reaction of 1,2-benzylidenedioxy-3-chloropropane with 1,3-diaminopropane and subsequent condensation of 1,2-benzylidenedioxy-7-amino-4-azaheptane with salicylaldehyde. Complexes of 1,2-benzylidenedioxy-7-(2-hydroxybenzylideneamino)-4-azaheptane with cobalt(II), nickel(II), and copper(II) salts were obtained. The structure of the ligand and its complexes was established on the basis of their elemental compositions, IR, UV, and H-1 NMR spectra, magnetic susceptibilities, and thermogravimetric data.
Keywords: Cu(Ii); Co(Ii); Ni(Ii)